Effect of hyperthermic intraperitoneal chemotherapy for gastric cancer patients: a meta-analysis of the randomized controlled trials. Issue 12 (December 2019) - Liu, Yan-Wen; Du, Ying; Chen, Bao-An
Objective: To determine the effectiveness and safety of hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with advanced gastric cancer and peritoneal metastases. Methods: PubMed®, CNKI, Web of Science, VIP and WANFANG databases were searched to identify randomized controlled trials (RCTs) that examined the effect of HIPEC on survival, clinical response and adverse events. Patients with advanced gastric cancer and peritoneal metastases were divided into an experimental group and a control group. The statistical results are presented as relative ratio (RR), mean difference (MD) and 95% confidence interval (CI). Results: Twenty-one RCTs met the inclusion criteria ( n = 1674 patients). Meta-analysis showed that the 3-year survival rate was significantly higher in the HIPEC group than in the control group (RR 1.61; 95% CI 1.43, 1.82) and the complete response rate was significantly higher in the HIPEC group than in the control group (RR 2.35; 95% CI 1.67, 3.31). HIPEC was also beneficial in terms of decreased CEA (MD −1.79; 95% CI −2.22, −1.35). There was no significant difference in the rate of adverse reactions (RR 1.00; 95% CI 0.87, 1.14). Conclusions: HIPEC had a beneficial effect on 3-year survival rate and complete response in patients with advanced gastric cancer and peritoneal metastases.